Customer Contributions to Quality: A Different View of the Customer-Oriented Firm - Lengnick‐Hall, Cynthia A. (Academy of Management Review, 1996)
Regardless of the specific tools and methods a firm adopts or what quality experts an organization follows, managing for quality and competitive advantage means a firm must become customer oriented. Unfortunately, many quality-management programs and efforts to enhance competitiveness take a rather limited view of potential customer involvement in the process. This article first examines familiar roles that customers play in both manufacturing and service organizations. Then, insights from organization theory, services marketing. strategic management, and total quality concepts are integrated to develop both a conceptual model and 10 propositions based on a more complex view of potential customer contributions to competitive quality. Both a research agenda and ideas for improved organizational practice are discussed.